Virtualization implementation approach for data centers to maximize performance - Uddin, Mueen; Abdul Rahman, Azizah; Shah, Asadullah; Memon, Jamshed (Asian Network for Scientific Information, 2012)
This study focuses on the implementation of virtualization technology in data centers to provide efficient solutions for increasing the efficiency and performance of data center. Data centers are the building blocks of IT business enterprises providing the capabilities of centralized repository for storage, management, networking and dissemination of data. With the rapid increase in the capacity and size of data centers, there is a continuous increase in the demand for energy consumption. These data centers not only consume a tremendous amount of energy but are riddled with IT inefficiencies. Data center are plagued with thousands of servers as major components. These servers consume huge energy without performing useful work. In an average server environment, 30% of the servers are “dead” only consuming energy, without being properly utilized. Their utilization ratio is only 5 to 10%. This study proposes a five step model using an emerging technology called virtualization to achieve energy efficient data centers. This process helps to make data centers green and energy efficient so as to ensure that IT infrastructure contributes as little as possible to the emission of green house gases and helps to regain power and cooling capacity, recapture resilience and dramatically reducing energy costs and total cost of ownership.